2009
DOI: 10.1103/physrevlett.102.186101
|View full text |Cite
|
Sign up to set email alerts
|

Subnanometric Near-Field Raman Investigation in the Vicinity of a Metallic Nanostructure

Abstract: We present a near-field Raman investigation in the subnanometric vicinity of a metallic nanotip, where the tip-sample distance is precisely controlled by our newly developed time-gated illumination technique. Using this scheme on an isolated carbon nanotube, we have profiled the spatial decay of evanescent light. We also investigated extremely short-ranged chemical and mechanical interactions between the metal on the tip apex and the molecules of an adenine sample, which are observable only within the subnanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 22 publications
1
101
1
Order By: Relevance
“…Kawata and colleagues, to generate high-resolution TERS images, demonstrated an interesting time-gated approach. With the AFM used for TERS operating in tapping mode and locked in on the oscillation frequency, they were able to image carbon nanotubes with nanometer spatial resolution [6]. This was possible due to the electric field being confined to a region within 3 nm of the tip.…”
Section: Experimental Ters Configurationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Kawata and colleagues, to generate high-resolution TERS images, demonstrated an interesting time-gated approach. With the AFM used for TERS operating in tapping mode and locked in on the oscillation frequency, they were able to image carbon nanotubes with nanometer spatial resolution [6]. This was possible due to the electric field being confined to a region within 3 nm of the tip.…”
Section: Experimental Ters Configurationsmentioning
confidence: 96%
“…Since the initial demonstration of tip-enhanced Raman scattering (TERS) more than a decade ago [1][2][3], significant progress has been made in our understanding of the mechanisms that give rise to these enhancements and also the utilization of these enhancements in a variety of applications. Some of the most impressive results include single nanometer resolution and single molecule detection [4][5][6][7]. A variety of different experimental configurations have been developed to address different chemical questions.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral resolution drastically improved from <100 nm of the initial studies down to the current single-molecule scale [23,24]. Developed techniques have been applied not only to single-molecule imaging [25], but also to the investigation of the phonon structure of an ultrasmall crystalline boundary [26], single-molecule switching [27], distribution of the electromagnetic field of a single metal nanorod, [28] and dynamics of vibration in an ultrashort timescale [29]. In a well-controlled ultrahigh vacuum environment at low temperature (<10…”
Section: Single-site Sers For Single-molecule Observationmentioning
confidence: 99%
“…Conventional SPP excitation schemes for NSOM measurements include prism coupling (Kreschtmann configuration) [56], grating coupling [72], NSOM probe coupling [73], and interactions between a metallic probe and a sample [71]. As introduced in Section 2, the stepgap leakage SPP generation scheme provides a controllable localized SPP source for NSOM probes, without strict requirements on the incident light source.…”
Section: Near-field Scanning Optical Microscopy (Nsom) Is a Powerful mentioning
confidence: 99%
“…Uncoated optical fiber probes can be made to 80 nm in diameter [70], and aperture probes typically have 40 nm-diameter aperture sizes [60]. Some reports showed that the resolution can be as high as 15 nm in the case of metallic probes [71].…”
Section: Near-field Scanning Optical Microscopy (Nsom) Is a Powerful mentioning
confidence: 99%